Cycle Index Formulas for D n Acting on Unordered Pairs - Muthoka, Geoffrey; Kamuti, Ireri; Lao, Hussein; Kimani, Patrick Mwangi (Uoem, 2015)
The cycle index of dihedral group D n acting on the set of X the vertices of a regular n- gon was studied (See [1]). In this paper we study the cycle index formulas of D n acting on unordered pairs from the set . In each case the actions of the cyclic part and the reflection part are studied separately for both an even value of and an odd value of .1.